Gut Microbiome Reveals Specific Dysbiosis in Primary Osteoporosis - Xu, Zhiming; Xie, Zheng; Sun, Jianguang; Huang, Shilei; Chen, Yangyang; Li, Chengxiang; Sun, Xing; Xia, Bicheng; Tian, Lingyang; Guo, Caijuan; Li, Feng; Pi, Guofu (Frontiers in Cellular and Infection Microbiology, 2020)
Object: Primary osteoporosis (PO) is the most common bone disease, which is characterized by decreased bone mass, damage of bone tissue microstructure, increased bone fragility and prone to fracture. Gut microbiome may be involved in bone metabolism of PO through gut–brain axis regulation of immune system and endocrine system, however, the specific mechanism is still unclear. The purpose of this study was to characterize the gut microbiome of patients with PO and its possible role in the occurrence and development of the disease. Methods: Fecal samples were collected from 48 PO patients and 48 healthy controls (HC). The composition of gut microbiome community was analyzed by 16s rDNA amplification sequencing, and the difference of gut microbiome composition between PO patients and HC individuals was compared. PICRUSt was also used to predict the biological function of gut microbiome in patients with PO, and to explore its possible role in the occurrence and development of this disease. The classification model is constructed by random forest algorithm so as to screen the key biomarkers. Result:The diversity of gut microorganisms in PO patients was significantly higher than that in HC group (p<0. 05) and there was significant difference in microbial composition in PO group. The abundance of Dialister (0.036 vs. 0.004, p<0.001) and Faecalibacterium (0.331 vs. 0.132, p<0.001) were significantly enriched which were the key flora related to PO. Although no significant correlation between bone mineral density and the richness of microbial communities is found, PICRUST results show that there are a wide range of potential pathways between gut microbiome and PO patients, including genetic information processing, metabolism, environmental information processing, cellular processes, human diseases and organic systems. Notably, the discriminant model based on dominant microflora can effectively distinguish PO from HC (AUC=93.56). Conclusions: The findings show that PO is related to the change of gut microbiome, especially the enriched Dialister and Faecalibacterium genera, which give new clues to understand the disease and provide markers for the diagnosis and new strategies for intervention treatment of the disease.